Growth performance and starch yield potential of arrowroot (Maranta arundinacea) from various locations in Thailand - SUPAPORN IEAMKHENG; SOMTOP SANTIBENCHAKUL; SUPATTRA POONPAERDCHON; BUNNY SOEM; NAJJAPAK SOOKSAWAT (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Ieamkheng S, Santibenchakul S, Poonpaerdchon S, Soem B, Sooksawat N. 2024. Growth performance and starch yield potential of arrowroot (Maranta arundinacea) from various locations in Thailand. Biodiversitas 25: 3750-3757. Arrowroot (Maranta arundinacea L.) is a tuberous type of medicinal that has high starch quality and good health benefits. This research studied the yield and growth characteristics of arrowroot samples from different 5 accessions in Thailand, along with their important properties for commercial use. Samples were collected from 5 field crops in Thailand: Tha Maka District, Kanchanaburi Province (Th-T-K); Sai Yok District, Kanchanaburi Province (Th-Sy-K); Ratchaburi Province (Th-RB); Chanthaburi Province (Th-Chan), and Sa Kaeo Province (Th-SK). The growth rate and yield of Thai arrowroot at 3, 6, and 9 months after planting were evaluated and the starch was extracted and characterized. During 3 months, there was only growth with no tuber yield; at 6 months, the arrowroot from Th-Sy-K had the highest growth rate and yield. The highest yields were at 9 months after planting, with the tuber weight per clump in the range of 596-2,980 g that produced 121.8-150.8 g of starch (8-10% yield). DNA fingerprinting analysis and the molecular study indicated no variation among the 5 accessions of arrowroot, indicating the uniformity and reliability of the samples. The results of the nutritional composition, the amounts of carbohydrates and amylose in the Th-Sy-K and Th-RB samples tended to increase with plant growth. At the same time, other contents, namely moisture, and lipid, decreased. The main component of the arrowroot starch was carbohydrate (87-91%), and the 9-month starch had high viscosity and heat-resistant values. In conclusion, arrowroot starch showed potential as a novel raw material for application in the food industry and possibly in cosmetic and pharmaceutical manufacturing.